Le manuscrit Paris, Bibliothèque nationale de France, gr. 1209. L'autographe de Theodore Hyrtakènos? - Caballero-Sánchez, Paula María (Peeters Publishers, 2014)
The scarce information that we have about the Palaeologan scholar Theodoros Hyrtakenos has been transmitted through the only codex preserving his writings, Parisinus graecus 1209. The palaeographical study of this codex shows that it was copied at the second decade of the fourteenth century, a period that coincides with his main activity as a teacher and a writer in Constantinople. This paper examines the handwriting and the scribe’s marginal notes and corrections in order to elucidate the question whether the Parisinus graecus 1209 is an autograph copy of Theodoros Hyrtakenos.
Keywords: Literatura bizantina; Byzantine literature; Byzantine studies; Byzantine paleography and codicology; Palaeologan era